Case report: Bilateral central serous chorioretinopathy-like abnormalities in a man with pulmonary arterial hypertension - Zhou, Xinrong; Zhang, Jingxiang; Gu, Limin; Zhou, Hao; Zhang, Jingfa (Frontiers in Medicine, 2022)
Background Pulmonary arterial hypertension (PAH) leads to progressive increases in pulmonary vascular resistance, right heart failure, and death if left untreated. Ocular complications secondary to PAH were less reported. In this study, we reported a case of bilateral visual loss and metamorphopsia in a patient with PAH, who developed central serous chorioretinopathy (CSCR)-like abnormalities and optic disc atrophy. Case summary A 45-year-old man presented with decreasing central vision and metamorphopsia in both eyes. He had a history of PAH and 6-year history of low-dose oral sildenafil treatment. Slit-lamp examination revealed prominent dilated and tortuous episcleral and conjunctival vessels. Ultrawide-field color picture showed retinal pigment epithelial mottling and atrophy in ring-like configurations. Ultrawide-field autofluorescence showed multiple irregular hyper-autofluorescence with a constellation-like pattern surrounding the optic nerve head and macular region. Optical coherence tomography angiography (OCTA) b-scan demonstrated CSCR-like changes. Swept-source optical coherence tomography (SS-OCT) analysis showed optic nerve atrophy with enlarged cup/disc ratio in right eye, which was confirmed with perimetry. Fluorescein angiography (FA) showed marked leakage of macula and optic nerve head with time, cystoid macular edema, early blocking with late staining of the flecks as shown in the backgrounds of infrared and autofluorescence, and mild leakage in peripheral retina. Indocyanine green angiography (ICGA) showed dilation, tortuosity and congestion of all vortex veins without obvious leakage. Conclusion Undertreated PAH may cause the congestion of the choroid and induce CSCR-like abnormalities.